PEMANFAATAN MEDIA YOUTUBE DALAM MENINGKATKAN KEMAMPUAN ISTIMA’ PADA BAHASA ARAB - claudya, devana sindi; Fadillah, Adya Nada (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
The development of digital technology has brought significant changes in the world of education, especially in the use of innovative learning media. One of the media that is now widely used is YouTube, a video-sharing platform that is very popular among Indonesian people, including students and college students. This article aims to examine the effectiveness of the use of YouTube media, especially Arabic films, in improving students' listening skills (maharah istima') in learning Arabic. The method used is a literature study by analyzing various literature and related research results. The results of the study show that the use of YouTube as a learning medium is able to provide a more contextual, interesting, and interactive learning experience. Through Arabic-language films, students not only gain new vocabulary and better pronunciation, but also understand the cultural context and real-life use of language. This media also increases student motivation, interest, and independence in learning. With flexible access and diverse content, YouTube is an effective and adaptive learning solution in the digital age. The integration of YouTube media in Arabic language learning is highly recommended to support the achievement of optimal listening skills competencies. أصبح استخدام اليوتيوب كوسيلة لتعلم اللغة العربية، خاصة في صقل مهارات الاستماع، ذا أهمية متزايدة في العصر الرقمي اليوم. تهدف هذه الدراسة إلى تقييم مدى فعالية استخدام الأفلام العربية على اليوتيوب في مساعدة الطلاب على تحسين مهارات الاستماع لديهم. أجريت الدراسة من خلال طريقة دراسة الأدبيات ، من خلال تتبع مختلف المصادر الأولية والثانوية ذات الصلة. تكشف نتائج هذه الدراسة أن الأفلام باللغة العربية على YouTube قادرة على مساعدة الطلاب على فهم اللهجات المختلفة وأنماط التجويد والفروق الدقيقة في الثقافة العربية بشكل أكثر واقعية. بالإضافة إلى ذلك ، ثبت أن هذه الوسائط قادرة على تعزيز الاهتمام بالتعلم وزيادة الدافع وتقوية مهارات الاستماع بشكل كبير مقارنة بالأساليب التقليدية. كما يوفر دمج YouTube في عملية تعلم اللغة العربية مرونة من حيث الزمان والمكان، فضلا عن إثراء تجربة التعلم من خلال العروض السمعية والبصرية التفاعلية والسياقية. لذلك يعد اليوتيوب أحد أدوات التعلم الفعالة والمبتكرة في دعم تطوير مهارات الاستيفاء للطلاب